Empowerment of Islamic Religious Extension Workers in Improving Religious Services in Simpang Ulim District, East Aceh Regency - Mujibaturrahmi; Asri, fiesca Maini (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2024)
This research aims to evaluate the Joint Decree of the Minister of Religion and the Head of the State Civil Service Agency Number 574 of 1999 and Number 178 of 1999 concerning Guidelines for the Implementation of the Functional Position of Religious Counselors and Their Credit Scores. Factors that encourage and hinder Islamic Religious Counselors in carrying out their duties and functions. Assessing the implementation of the duties of Islamic Religious Counselors in the community. This research with a gradual approach was carried out using interview data collection methods, FGDs, and documentation studies. Field data collection was carried out from April to May 2023 in Simpang Ulim District, East Aceh Regency. The research results show that Islamic Religious Counselors understand the contents of Decree Numbers 574 and 178 of 1999, but have not consistently implemented them in their duties. The Indonesian Ministry of Religion's empowerment of extension workers is still very limited so that its human resources are very limited and not very ready when dealing with a more dynamic society. So far, the number of Islamic religious instructors has not been comparable to the population in Simpang Ulim District, East Aceh Regency. Monitoring from the central Ministry of Religion to extension workers and the target community is not carried out so the results cannot be known in the community. Then, the facilities and infrastructure prepared by the government are very limited, thus hampering the performance of extension workers in the field.